Electrospun MnCo2O4 nanofibers for efficient hydrogen evolution reaction. (13th September 2016) - Wu, Cong; Li, Chuang; Yang, Boyu; Zhou, Siyuan; Shi, Dingcong; Wang, Yanbo; Yang, Guocheng; He, Jin; Shan, Yuping
Abstract: MnCo2 O4 nanofibers (MCNFs) were successfully synthesized by electrospinning followed by a calcination process under mild conditions. The structural and morphological characterizations of MCNFs were performed by x-ray powder diffraction (XRD), thermogravimetric analysis (TGA), Raman spectroscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The electrochemical method was used to measure the electrocatalytic hydrogen evolution reaction (HER) properties of MCNFs. Electrochemical studies show that the developed MCNFs possess excellent electroactivity towards HER with low hydrogen-evolution overpotential and a small Tafel slope. In addition, electrospinning can promote the materials into nano-sized architectures with large surface area, which can effectively enhance the electrocatalytic HER properties of MCNFs.